Cipacinoids E–O: Eleven limonoids represent two different scaffolds from Cipadessa cinerascens. (1st January 2022) - Yu, Jin-Hai; Zhou, Bin; Wu, Pei-Qian; Liu, Qun-Fang; Yue, Jian-Min
Abstract: Eleven new limonoids named cipacinoids E–O (1 –11 ) including nine methyl angolensate-type limonoids (1 –9 ) and two havanensin-type limonoids (10 and 11 ), as well as seven reported limonoids (12 –18 ), were isolated from the leaves of Cipadessa cinerascens . The structures of these limonoids were identified by analyses of spectroscopic data and by using the methods of quantum-chemical calculation. Cipacinoids E–G (1 –3 ) are the first cases possessing an additional six-membered lactone ring formed by intramolecular transesterification between 9-OH and C-7 methyl ester. Graphical abstract: Image 1